PENGARUH FAKTOR-FAKTOR EKONOMI TERHADAP PREFERENSI PEKERJAAN MAHASISWA - Adam Maulana; Salsabila Nuriarti; Hanifah Iman; Mukhlisotul Jannah; Wahyu Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to investigate the relationship between economic factors and job preferences among students. The purpose of this research is to analyze the extent to which economic factors influence students' job preferences. The sample consisted of 30 student participants who completed a questionnaire assessing economic factors and their job preferences. Data were analyzed using descriptive statistics, correlation analysis, and validity testing using the SPSS software. The findings revealed a significant positive relationship between economic factors and job preferences among students (r = 0.556, p > 0.05). The correlation analysis indicated that economic factors have a strong influence on students' job preferences. The validity testing also confirmed the validity of both constructs, namely economic factors and job preferences. In conclusion, this study uncovers the significant role of economic factors in influencing students' job preferences. These findings provide a deeper understanding of the importance of economic factors in students' career choices. The practical implications of this research highlight the importance of considering economic aspects in the development of career guidance programs to assist students in making informed career decisions.